Using ecological and life-history characteristics for projecting species' responses to climate change - Sven Pompe; Jan Hanspach; Franz W. Badeck; Stefan Klotz; Helge Bruelheide; Ingolf Kühn (Frontiers of Biogeography)
Assessing the impact of climate change on range dynamics is difficult in the absence of large-extent distribution data. We developed a novel two-step approach as an instrument for biodiversity risk assessment. First, we established relationships between modelled loss of occupied grid cells (‘range loss’, R2=0.29), or gain of currently unoccupied grid cells (‘range gain’, R2=0.30), for 195 plant species with distributional data under the A1FI climate change scenario up to 2080, and ecological and life history traits (life form, leaf persistence, ecological strategy, pollen vector, Ellenberg indicator values and characteristics derived from species’ ranges). Secondly, we used the resulting coefficients to predict climatic sensitivity for 688 plant species without spatially explicit distributional information. The models predicted range losses of 34±20 % (mean±standard deviation) and range gains of 3±4 %. Specifically, measures of species’ distribution, such as range size, were significantly related to both range loss and range gain. Other traits associated with range loss (e.g. life form, number of floristic zones) were not necessarily related to range gain (instead related to Ellenberg temperature indicator), indicating that two distinct sets of ecological processes govern range expansion and contraction. We found interaction effects between moisture indicator values and life form for range loss, and between moisture and temperature indicator values for range gain. The responses of species to climate change are complex and context dependent. Thus, our results highlight the importance of incorporating trait interactions in models to assess risks of climate change.